(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: Pulmonary tuberculosis most commonly develops and often becomes generalized among HIV-infected patients. HIV-positive individuals present extra-pulmonary forms of tuberculosis twice as often as HIV-negative individuals. Purpose: To determine the frequency of ocular pathology and the relationship between ocular pathology and CD4 cell count in HIV-positive patients with tuberculosis. Materials and Methods: Three thousand and eighty four patients with pulmonary tuberculosis including 320 (10.4%) patients co-infected with HIV underwent examination at the City Tuberculosis Dispensary between 2014 and 2016. Results: Allergic or toxic retinal vasculitides and peripheral focal chorioretinitis of tuberculous etiology in either active or inactive inflammatory phase were most common ocular disorders among HIV-positive patients with marked immune deficiency. In these patients, median CD4 cell count was ≤200-300 cells/mm3 compared to the norm of 1600 cells/mm3.